2011
DOI: 10.1017/s204579601100045x
|View full text |Cite
|
Sign up to set email alerts
|

The CBCL 1.5–5 and the identification of preschoolers with autism in Italy

Abstract: Aims.To study the potential use of child behaviour checklist (CBCL) 1.5–5 scales for the early identification of preschoolers at risk of autism.Methods.CBCL scores of three groups of preschoolers were compared: (1) an experimental group of 101 preschoolers with autism spectrum disorder (ASD); (2) a control group of 95 preschoolers with other psychiatric disorders (OPD); (3) a control group of 117 preschoolers with typical development (TD). One-way analysis of variance (ANOVA), logistic regression with odds rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
78
1
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 34 publications
11
78
1
6
Order By: Relevance
“…Similarly, an increased risk of autism was found in offspring of mothers who had autoimmune thyroiditis during pregnancy (36); however, it was not clear whether the effect took place after birth due to the already transferred placental antibodies or during intrauterine growth. Diagnosis of autism was made by using ICD-10 clinical diagnosis in both studies by Brown et al (36) and Anderson et al (31) while Roman et al (26) used validated parent-reported instruments (CBCL 1.5-5 and SRS) (39). The additional strength of the study by Brown et al (36) is the use of matched controls and the ability to examine a wide range of offspring up to age 20.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an increased risk of autism was found in offspring of mothers who had autoimmune thyroiditis during pregnancy (36); however, it was not clear whether the effect took place after birth due to the already transferred placental antibodies or during intrauterine growth. Diagnosis of autism was made by using ICD-10 clinical diagnosis in both studies by Brown et al (36) and Anderson et al (31) while Roman et al (26) used validated parent-reported instruments (CBCL 1.5-5 and SRS) (39). The additional strength of the study by Brown et al (36) is the use of matched controls and the ability to examine a wide range of offspring up to age 20.…”
Section: Discussionmentioning
confidence: 99%
“…Der "Total Problem Score" eignet sich zudem ausgezeichnet als Screening für psychische Erkrankungen des Kindes und Jugendalters [51]. Die Vorgabe der CBCL erwies sich bei der Identifikation einiger psychischer Erkrankungen, wie beispielsweise Autismus-Spektrum-Störung [39], ADHS [21], und Zwangsstörungen [49] als nützlich. Obwohl die CBCL-Skalen nicht zur Erfassung von Dissoziation und PTBS entwickelt worden sind, erscheint die Vorgabe der CBCL und des YSR auch bei PTBS im Sinne eines Breitbandscreenings als sinnvoll.…”
Section: Introductionunclassified
“…En ese sentido el CBCL 1.5-5 es uno de los instrumentos para medir la psicopatología más validados en distintos países [2][3][4][5] . Además, la uniformidad de la metodología usada por los investigadores para evaluar las propiedades psicométricas del CBCL ha hecho que la comparación transcultural sea posible 6 .…”
unclassified